1999
DOI: 10.1046/j.1365-2141.1999.01649.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of p53 dysfunction on purine analogue cytotoxicity in chronic lymphocytic leukaemia

Abstract: Summary. To clarify the role of p53 in the killing of chronic lymphocytic leukaemia (CLL) cells by purine analogues, we examined the cytotoxic effects of chlorodeoxyadenosine and udarabine on CLL cells that had been characterized according to their p53 functional status.Cases of CLL with p53 dysfunction (n 7) displayed slight, but signi®cant, resistance to nucleoside-induced cell killing when compared with cases with functionally intact p53 (n 12). The small difference between the two groups indicated that p53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 11 publications
3
28
0
Order By: Relevance
“…These observations have been made in in-vitro experiments (Silber et al, 1994;Morabito et al, 1997;Pettitt et al, 1999b;Sturm et al, 2003), in retrospective clinical studies (el Rouby et al, 1993;Wattel et al, 1994;Dohner et al, 1995;Valganon et al, 2005) and most importantly in prospective clinical trials of first-line therapy (Catovsky et al, 2004;Gine et al, 2005;Stilgenbauer, 2005). In the light of these considerations, it is clear that one of the most pressing therapeutic challenges in CLL is to devise new and better ways of treating patients with p53 defects.…”
Section: Introductionmentioning
confidence: 96%
“…These observations have been made in in-vitro experiments (Silber et al, 1994;Morabito et al, 1997;Pettitt et al, 1999b;Sturm et al, 2003), in retrospective clinical studies (el Rouby et al, 1993;Wattel et al, 1994;Dohner et al, 1995;Valganon et al, 2005) and most importantly in prospective clinical trials of first-line therapy (Catovsky et al, 2004;Gine et al, 2005;Stilgenbauer, 2005). In the light of these considerations, it is clear that one of the most pressing therapeutic challenges in CLL is to devise new and better ways of treating patients with p53 defects.…”
Section: Introductionmentioning
confidence: 96%
“…[180][181][182][183][184][185][186][187] Alterations in p53 function have been related to in vitro Leukemia resistance to NA. 68,188 p53 appears to have a specific role in resistance to NA since it possesses exonuclease activity, and may therefore be able to excise illegally DNA-incorporated NA. Recently, Feng et al reported that although the 3Ј-5Ј exonuclease of wild-type p53 (wt-p53) protein was able to bind and excise gemcitabine residues from DNA in vitro, removal of the drug molecules from cellular DNA was slow in sensitive cells containing wt-p53, and undetectable in drugresistant mut-p53 cells.…”
Section: Defective Cell Death Pathways and P53 Exonuclease Activitymentioning
confidence: 99%
“…Incorporation of 2-CdATP into DNA by the repair machinery terminates the nucleotide excision repair process leading to the progressive accumulation of DNA single-strand breaks which eventually initiate apoptosis by p53-dependent or p53-independent pathways. 67,68 p53 activation subsequently regulates the levels of expression of p53-dependent proteins such as Bcl-2 and Bax leading to the activation of the caspase pathway. 69 Second, incorporation of 2-CdA into DNA may alter gene transcription with a consequent depletion of proteins required for cell survival.…”
Section: Figurementioning
confidence: 99%
“…Furthermore,¯udar-abine was found to be e cient in the treatment of chronic lymphoid leukaemia with low proliferative capacity, suggesting that it may also trigger apoptosis. In fact,¯udarabine induces the expression of the proapoptotic protein p53 (Chernova et al, 1995), and cells carrying an inactivating mutation of p53 have been reported to be resistant to¯udarabine (Pettitt et al, 1999;Thomas et al, 1996). Another possible target for¯udarabine is STAT1, a transcription factor that is involved in cellular responses to interferon (IFN).…”
Section: Introductionmentioning
confidence: 99%